4G coverage in Malaysia - Ab Aziz, Nur Faizah; Mohamad Ali, Noor Azian (International Journal of Science and Research (IJSR), 2015)
Mobile phone is changing the way the world communicates. In the early 1990s, only one per cent of the world's population owned a mobile phone but today almost all using mobile phone to make phone calls and sending text message. 4G is one of the fastest growing technologies currently available with higher data consumption and increased connectivity. Malaysia continues to grow in tandem, riding on the telecommunications service evolution over the last 10 years. This includes a firm grounding for high-speed connection in the last few years. In this paper, we will discuss on 4G provided by Malaysia service providers.